Home Management of Children With COVID-19 in the Emilia-Romagna Region, Italy - Vergine, Gianluca; Fantini, Michela; Marchetti, Federico; Stella, Marcello; Valletta, Enrico; Biasucci, Giacomo; Lanari, Marcello; Dodi, Icilio; Bigi, Maurizio; Magista, Anna Maria; Vaienti, Francesca; Cella, Andrea; et al. (Frontiers in Pediatrics, 2020)
In most children, coronavirus disease 2019 (COVID-19) is a mild or moderate disease. Moreover, in a relevant number of cases, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remains totally asymptomatic. All these findings seem to suggest that otherwise healthy children with suspected COVID-19 might be managed in the community in most cases, thus avoiding hospital admission and closely related medical, social and economic problems, including overwhelming hospitals. Unfortunately, home management of children with suspected COVID-19 rarely occurs, and many children with suspected or laboratory-confirmed SARS-CoV-2 infection are frequently hospitalized irrespective of the severity of disease. To evaluate the role of community health services (CHSs) in the management of children with COVID-19, 1,009 children with suspected SARS-CoV-2 infection were studied in Emilia-Romagna Region, Italy. Among them, 194 (19.2%) resulted positive for SARS-CoV-2. The majority (583, 58%) were tested at home by CHSs, while 426 (42%) were brought to the hospital for testing. The patients who were managed in the hospital had a significantly lower median age than those who were managed at home (2 vs 12 yrs, p<0.001). Family exposure was significantly more frequent among those who were managed at home (82% vs 46%, p<0.05). The clinical findings were similar between the children who were managed at home and those who were managed in the hospital. Only one of the children managed at home (0.7%) required hospitalization; in comparison, 26 (48%) of those whose swab samples were taken at the hospital were hospitalized. Our research shows for the first time the importance of CHSs in the management of COVID-19 in children; because of the high frequency of mild to moderate cases, management by CHSs can reduce the care load in hospitals, providing enormous advantages on the familial, medical, social, and economic levels. These findings could be useful for suggesting a territorial rather than hospital-based strategy in pediatrics in the case of a new wave of the epidemic.